Case Reports of Aripiprazole and Problematic Gambling in Schizophrenia: A Critical Review of the Evidence. Issue 4 (July 2019) - Lachance, Alexandre; Corbeil, Olivier; Corbeil, Stéphanie; Chalifour, Guillaume; Breault, Ann-Sophie; Roy, Marc-André; Demers, Marie-France
Abstract: Background: Pharmacovigilance studies have reported a higher risk of problematic gambling (PG) in people receiving aripiprazole (ARI), a partial dopamine agonist. This association needs to be specifically assessed in schizophrenia (SZ) given the high prevalence of risk factors for PG in this population (eg, comorbid substance use) and given the nature of the dopamine dysfunction in this disorder. At the present stage, case studies may shed light on such an association. Methods: All published cases involving SZ patients with PG while on ARI were systematically identified. Two instruments were used to assess causality. Results: We identified 16 published SZ cases exposed to ARI experiencing PG. Half of whom had a gambling history before ARI exposition. Naranjo scores led to the estimation of a possible link between ARI exposition and PG in 15 of 16 cases (average score of 3) and probable (score of 5) in 1 case. More than 50% of items were left unknown owing to the lack of information or scale limitations. Using the Liverpool algorithm, causality estimation was raised to probable in 13 of 16 cases, definite in 1 case, and nonassessable in 2 cases. Conclusions: The present review confirms that ARI may be involved in the occurrence of PG in some SZ patients. However, important information to assess causality was frequently missing, and the 2 scales used did not yield the same degree of certainty. The current article calls for including more details in future case reports and for well-powered studies carefully assessing factors such as comorbid diagnoses. Abstract : Supplemental digital content is available in the text.